The Intergenerational Relations in the "Rebirth" of Lithuania - Šerpetis, Kęstutis (Sociologija. Mintis ir veiksmas, 1997)
The article analyzes the intergenerational relations in the formation of the Lithuanian state. The author claims that the paradox of Singing Revolution is that the activists of the movement were not from the younger generations. Rather, youth played a limited role not only in the revolutionary movements but also in the later political life. The author attempts to understand the orientations of behaviour through an analysis of the processes of socialization.
Keywords: movement of independence; generation; socialization; intergenerational relations